Diaphragmatic hernia after pediatric living donor liver transplantation: An Indian experience with review of literature - Bramha Pattnaik; Piyush Kumar Sinha; Nilesh Patil Sadashiv; Nihar Mohapatra; Viniyendra Pamecha (Wolters Kluwer Medknow Publications, 2021)
Aim: Although intestinal obstruction following living donor liver transplantation (LDLT) is relatively common, diaphragmatic hernia (DH) as the attributing cause is rarely reported. The study aimed to find out the incidence, clinical presentation, and management of DH after liver transplant in pediatric patients. Materials and Methods: A retrospective review of all cases of pediatric liver transplants was performed. Case sheets, operation records, and investigations including radiology were studied. Results: Out of 79 cases of pediatric liver transplants, two cases of posttransplant DH were identified. The first case is a 2-year-old male child who was transplanted for progressive familial intrahepatic cholestasis, and the second one is a 4-year-old boy who underwent LDLT for hepatitis A-induced acute liver failure. The first child presented abdominal symptoms and the second one with pulmonary symptoms. The DHs were diagnosed at 132 and 70 days, respectively, posttransplant by chest radiographs and computed tomography scan. The defects were located at the posteromedial aspect of the diaphragm in both the cases and were closed by primary closure with mesh reinforcement. Both the children are doing well with no recurrence. Conclusion: High index of clinical suspicion is mandated in pediatric patients after liver transplant and once the diagnosis is confirmed, urgent surgical exploration is mandatory.